Respon Pertumbuhan Dan Produksi Tanaman Kacang Hijau (Vigna radiata L.) Terhadap Pemberian Jenis Dan Dosis Pupuk Kandang Berbeda: - - Andreas Peka Banda; Marten Umbu Nganji; Lusia Danga Lewu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2021)
This study aims to determine the growth response and yield of mungbean (Vigna radiata L.) on the application of cow and goat manure. This research was conducted from October to December 2021 in Mbatapuhu Village, Haharu District, East Sumba Regency. This study used a non-factorial completely randomized design (CRD) which was repeated three times. The treatments studied were 5 doses of cow manure (S0= 0 t/ha, S5=5 t/ha, S10=10 t/ha, S15=15 t/ha and S20=20 t/ha) and 5 doses of manure. goats (K0=0 t/ha, K5=5 t/ha, K10=10 t/ha, K15=15 t/ha and K20=20 t/ha), so that each treatment of manure contained 15 treatment units. The results showed that the use of cow or goat manure was very influential on the growth and yield of mungbeans. The best dose of cow manure was obtained in the S20 treatment (20 tons/ha), while the goat manure was in the K15 treatment (15 tons/ha). The use of cow manure at a dose of 20 t/ha gave the best results in the number of pods/plant, number of seeds/plant, weight of seeds/plant and weight of 100 seeds, respectively 86.67 pods, 941.00 grains, 90.00 gr/ plants and 11.67 g/100 seeds, while for goat manure the best dose of 15 tons/ha, each gave yields of 95.34 pods, 956.67 grains, 79.99 g/plant and 17.22 g/ 100 seeds. Cow and goat manure has the potential to be used as a source of plant nutrients in an effort to increase yields. Keywords: Cow and goat manure, nutrient sources, mungbeans, increased yield.